Identifikasi Penentuan Skala Prioritas Penanganan Banjir Di Kecamatan Koto Tangah Kota Padang - Aisyah Salsabila; Hary Febrianto; Heny Mariati (Universitas Tamansiswa Padang, 2025)
Determining the priority scale for handling inundation or flooding in Koto Tangah District is very important to optimize the use of resources, minimize social and economic impacts, and improve the effectiveness of mitigation measures. This study aims to (1) determine the extent of the area affected by flooding in Koto Tangah District, Padang City; and (2) determine the priority scale for flood management in Koto Tangah District, Padang City. The data processing method used to determine the extent of flood-affected areas employed the Backscattering Thresholding Algorithm obtained from Google Earth Engine (GEE), utilizing ArcMap 10.8 software for flood area calculation. To determine the priority scale for flood management, a scoring method and hierarchical quantitative analysis were applied using a Geographic Information System (GIS). Based on the research results, it can be concluded that the flood-affected area in Koto Tangah District covered 9.92 km², with two villages having the largest flood impacts, namely Dadok Tunggul Hitam Village and Parupuk Tabing Village. The results of determining the flood management priority scale showed that the highest scores were obtained by Batipuh Panjang Village and Lubuk Buaya Village, which were categorized as Priority 1.